Laparoscopic versus open hepatectomy for large hepatocellular carcinoma: a single center propensity-score-matching comparative analysis of perioperative outcomes and long-term survival - Dumronggittigule W. (2023)
Background: Although the benefits of laparoscopic hepatectomy (LH) for hepatocellular carcinoma (HCC) in most circumstances are evident, the benefits for large HCC are contentious. This study aimed to compare the perioperative outcomes and survival after LH versus open hepatectomy (OH) in large HCC patients. Methods: An analysis of prospectively maintained database included 215 hepatectomies for large HCC (diameter ≥ 5 cm). The operative and survival outcomes were compared between the LH group (n = 109) and the OH group (n = 106). Propensity score matching (PSM) 1:1 included 70 patients in each group. The entire cohort multivariable analyses were performed to identify the factors associated with surgical complications and suboptimal recurrence-free survival (RFS). Results: After PSM, baseline characteristics and the extent of liver resection were similar in both groups. The LH group had a shorter hospital stay than the OH group (7 vs 9.5 days, p = 0.001). The R0 resection rate, complication rate, overall survival, and RFS were similar between the groups. The multivariate analyses revealed two independent factors predicting surgical complication (major resection; p < 0.001 and large volume blood loss; p = 0.042), and 3 independent factors predicting suboptimal RFS including R1 resection (p = 0.011), multifocal HCC (p = 0.005), and microvascular invasion (p = 0.001). LH was not associated with surgical complication and suboptimal RFS. Conclusion: Our study highlights the benefits of LH by improving the perioperative outcomes, without long-term survival inferiority in selected large HCC patients compared with conventional OH. LH can be an attractive option for large HCC treatment. Graphical abstract: [Figure not available: see fulltext.].